Examining User Opinions, Satisfaction Levels, and Challenges Towards Institutional Repository: An Empirical Study - Hurum, Uzila; Mahawar, K. L.; Shimray, Somipam R. (DESIDOC Journal of Library & Information Technology, 2024)
This study investigates user opinion, satisfaction level, and challenges towards institutional repositories. The researchers adopted survey method, questionnaire tools, and simple random sampling techniques and collected 548 respondents from the autonomous institutions of the department of science and technology. The mean analysis on opinion towards the benefits of an institutional repository reveals that “It promotes self-archiving 24*7” hasthe highest mean score, while concerning the satisfaction level of users “I am satisfied with membership facility” has the highest mean score, and vis-à-vis overall problems “Electricity problem” has the highest mean score. The result indicates that age has a significant difference with library facility (p=.001), retrieval (p=.000), searching and browsing facility (p=.001), usability (p=.012), and copyright issue (p=.002). Concerning respondent’s designation, there is a significant difference in the library facility (p=0.027), retrieval (p=0.001), usability (p=0.005), awareness problem (p=0.005), and copyright issues (p=0.001). This study bridged the existing literature gap by determining various factors affecting users’ opinions, satisfaction levels, and overall problems. Further, examine the significant difference between demographic variable and study variables.